Happy retirement Mr. Rasaya Marimuthu / Rofiza Aboo Bakar - Aboo Bakar, Rofiza (Academy of Language Studies, 2023)
This retirement marks the end of a chapter. The words you have written in the story are powerful and encouraging. As you begin the next chapter, we wish you well. May your story be even more inspiring. You are such a gem! You have left a good legacy of a commendable work ethic and excellent service. We will be forever grateful for the great work relationship we have had with you and hope you enjoy this much-deserved rest.